ANALISIS PENERAPAN E-BILLING DALAM PENYETORAN PAJAK PADA SATUAN KERJA STASIUN GEOFISIKA GUNUNGSITOLI - Nainggolan, Firmatogu; Bate'e, Maria Magdalena; Waruwu, Eliyunus (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This research analyzes how e-billing is implemented in paying taxes at the Stasiun Geofisika Gunungsitoli. The research method used a qualitative method with a descriptive approach. Primary data was obtained through interviews and secondary data was obtained from official documents, related literature, and other relevant information sources. The research results show that tax payments at the Stasiun Geofisika Gunungsitoli have implemented e-billing, payments are made at the Gunungsitoli Post Office using cash payments and there are still delays in tax deposits. There are several obstacles to implementing e-billing at the Stasiun Geofisika Gunungsitoli, which include not being able to carry out Internet banking transactions due to not having an Internet banking token, the Internet network being unstable or slow, long queues at the post office payment counter, ATM receipts/proof of payment are easily erased, and lack of socialization regarding tax e-billing. Based on these findings, this research recommends that the Stasiun Geofisika Gunungsitoli strive to accelerate the implementation of electronic payment transactions so that tax payments can be made more quickly and easily, can be done anywhere, and avoid delays in tax deposits. It is also necessary to better understand the regulations for paying taxes to avoid tax sanctions. Keywords: E-billing; Tax Deposit; Electronic Tax Payment Application